Rancang Bangun Sistem Informasi Bengkelku.com Berbasis Web Untuk Meningkatkan Penjualan - Imam Baihaki; Muhammad Setiyawan; Riyan Abdul Aziz (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Bengkelku.com is a trading company engaged in the promotion and sale of motorcycle spare parts, such as: mufflers, motorcycle lights, spark plugs, mirrors, etc. Where the promotion process and others are still conventional. Which means the customer has to come to the workshop to purchase the product. The design of the web-based workshopku.com information system is a step to increase product promotion and sales. So that it can provide benefits for the workshop. The aim of building a workshop information system is that customers can order products without having to come to workshopku.com, the repair shop can solve the problem of managing orders, thus making it easy for consumers to get information about products available at workshopku.com. This system is designed using the programming language HTML, PHP, using the MYSQL database. While the editor uses Visual Studio Code. With the implementation of the information system workshopku.com has been successful and according to the needs of customers who want to get information quickly and accurately.